Investigation of formicary corrosion in copper tubes used for air conditioning ... [et al.] / [microfilm] - 360668 Phua, Sewee (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Engineering (Mechanical) - University Teknologi Malaysia, 2002